Feasibility Analysis of a Methanol Fuelled Bulk Carrier - Adami, Giorgia; Figari, Massimo (Modelling and Optimisation of Ship Energy Systems 2023, 2023)
Emissions restrictions are growing worldwide due to climate change concern. In the maritime sector different fuels are under scrutiny to identify the best option toward a carbon free transport. Methanol, the simplest alcohol, is one of the most discussed alternative fuels. This work aims at investigating the use of this chemical as fuel on board from different perspectives in order to provide a complete picture. A 34000 DWT bulk carrier has been used as case study including both the hypothesis of a retrofit and a newbuilding. From the technical point of view the attention has been focussed on the ship general arrangement finding space for methanol tanks and fuel systems, in agreement with the existing ABS rules. A carbon footprint emission assessment has been performed, taking into account both IMO’s and EU’s regulations. To have a more complete overview, a preliminary economic evaluation is also performed with the estimation of OpEx and CapEx related to the methanol system on board. Results showed the technical feasibility with respect to the ship conversion and some criticality related to safety measures and the energy content of methanol. From the polluting impact point of view, the study highlights the importance of a Well to Wake (WtW) approach instead of considering only Tank to Wake (TtW) emissions. From this perspective, with a global decrease in GHG emissions of about 85% with respect to HFO, green methanol appears to be the only viable ecological solution. The use of bio methanol on board significantly affects OpEx, with an estimate increase of more than 250%, due to the high costs of methanol produced from renewable feedstocks and its small production worldwide.